Anti-HF photoresist-removing alkali-soluble photoresist and preparation method thereof
By introducing silicon oxygen bonds and rigid fluorine-containing groups into the photoresist, combined with modified nanotitanium dioxide, to form a tight stacked structure, the problem of photoresist shedding and contamination during high-concentration hydrofluoric acid etching is solved, and efficient degluing and alkali-soluble properties are achieved, improving the resolution and environmental friendliness of the pattern.
Patent Information
- Application Number
- CN202510096739.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Existing photoresist is prone to fall off during the etching process of high concentration hydrofluoric acid, which leads to the impact of the imaging process, and the cured glue in the degluing process is insoluble, which easily contaminates the chain lithography machine and increases the risk of environmental pollution.
By introducing silicon oxygen bonds and rigid fluorine-containing groups, phenolic resins and acrylates are modified, combined with modified nanotitanium dioxide, forming a tight stacked structure, improving the hydrofluoric acid resistance, and fully filling the resin voids through nanotitanium dioxide to improve alkaline dissolution rate and degluing performance.
The stability and glue removal performance of photoresist in high-concentration hydrofluoric acid etching are improved, reducing pollution and environmental impacts, while improving the resolution and integrity of the pattern.
Smart Images

Figure CN119805863A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photolithography, in particular to an alkali-soluble photoresist resistant to HF stripping and a preparation method thereof. Background Art
[0002] Photoresist, also known as photoresist, can undergo cross-linking, curing or degradation reaction when exposed to light beams. It is a light-sensitive mixed liquid composed of three main components: photosensitive resin, photosensitizer and solvent. Photoresist has photochemical sensitivity and uses photochemical reactions to transfer the required fine patterns from a template (mask) to the substrate to be processed through processes such as exposure and development, and then undergoes processing such as etching, diffusion, and ion implantation.
[0003] Photoresist is a key material used to make chip graphic patterns in semiconductor manufacturing. It undergoes a chemical reaction in the exposed area, resulting in a significant difference in solubility between the exposed and non-exposed parts in alkaline solution. After being treated with an appropriate solvent, the soluble part is dissolved to obtain the desired image. According to different imaging mechanisms, photoresists can be divided into negative photoresists and positive photoresists. Positive photoresists are photoresists that decompose under a certain wavelength of light, increase their solubility, and increase the difference in solubility between the exposed and non-exposed parts. The exposed soluble part can be removed with an appropriate developer, and finally an image consistent with the mask is formed on the processed surface.
[0004] At present, photoresist systems are divided into phenolic, cyclized rubber, acrylic and polyimide systems. In the prior art, only cyclized rubber system photoresist can meet the requirements of hydrofluoric acid etching liquid. However, the common cyclized rubber system negative photoresist is not water-soluble, and the required developer is an organic developer, and the addition of an organic rinse solution causes great pollution to the environment.
[0005] In the chain photolithography machine for photovoltaic applications, mask glue that can resist high concentration of hydrofluoric acid is a large category. If it cannot resist a certain concentration of hydrofluoric acid solution during the etching process, it will cause the photoresist to fall off, thereby affecting the imaging process. In addition, if the cured glue in the debonding process is insoluble and adheres to the roller of the chain machine, it will contaminate the back of the silicon wafer, making subsequent cleaning difficult, and at the same time will produce solid waste problems, thereby polluting the environment.
[0006] Therefore, a HF-stripping-resistant alkali-soluble photoresist and a preparation method thereof are proposed. Summary of the invention
[0007] The invention aims to provide a HF-resistant alkali-soluble photoresist and a preparation method thereof. The invention comprises the following steps: a modified phenolic resin is obtained by introducing a silicon-oxygen bond, a modified acrylate is obtained by adding a fluorine-containing acrylate monomer, the modified phenolic resin, the modified acrylate, propylene glycol methyl ether acetate, a photosensitive substance and an auxiliary agent are stirred, dispersed, filtered and impurized to obtain a photoresist colloid, and the photoresist colloid and modified nano titanium dioxide are stirred, dispersed and impurized to obtain a hydrofluoric acid-resistant alkali-soluble photoresist; rigid silicon-oxygen groups and rigid fluorine-containing groups are introduced, and the stacking ability between the rigid conjugated systems of benzene rings is utilized to form a tight stacking layer, thereby increasing the hydrofluoric acid resistance; and modified nano titanium dioxide is added, and after the nano titanium dioxide is acid-etched, the gaps in the photoresist resin structure cannot be fully filled, and water and alkali molecules penetrate through the gaps into the resin structure, thereby increasing the alkali dissolution rate and increasing the alkali-soluble performance of the photoresist after acid etching.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention provides a HF-resistant and alkali-soluble photoresist, which comprises a photoresist colloid and modified nano titanium dioxide;
[0010] The photoresist colloid comprises 45-75 parts of modified phenolic resin, 12-25 parts of modified acrylate, 5-15 parts of photosensitizer, 160-240 parts of solvent and emulsion auxiliary agent;
[0011] The modified phenolic resin is prepared by a phenol compound, an aldehyde compound and a modifier 1; the modified acrylate is prepared by styrene acrylate, acrylic acid and a modifier 2;
[0012] The mass ratio of the photoresist colloid to the modified nano titanium dioxide is 8-12:1;
[0013] The emulsion auxiliary agent includes silicone oil and antioxidant 1010.
[0014] Preferably, the viscosity of the photoresist is 500-800 mPa·s; the molecular weight of the modified phenolic resin is 5000-10000; the molecular weight of the modified acrylate is 1000-2000; and the coating thickness of the photoresist is 10-25 um.
[0015] Preferably, the phenol compound is selected from one of α-naphthol, nonylphenol, phenol and phenylphenol; the aldehyde compound is selected from one of salicylaldehyde, formaldehyde and furfural; and the molar ratio of the phenol compound to the aldehyde compound is 1:1.2-1.8.
[0016] Preferably, the mass ratio of the modified phenolic resin to the modified acrylic ester is 1-5:1; and the solvent is propylene glycol methyl ether acetate.
[0017] Preferably, the first modifier is selected from one of terminal hydroxyl polydiphenylsiloxane, terminal hydroxyl polyphenylmethylsiloxane and terminal hydroxyl polydimethylsiloxane; the second modifier is selected from one of hexafluorophenylpropyl methacrylate, perfluorooctyl ethyl acrylate and methacrylic acid.
[0018] Preferably, the photosensitizer is a mixture of 2-hydroxy-2-methyl-1-phenylpropanone and sodium diazonaphthoquinone sulfonate; the mass ratio of the 2-hydroxy-2-methyl-1-phenylpropanone to the sodium diazonaphthoquinone sulfonate is 1-5:1.
[0019] The present invention also provides a method for preparing the HF-resistant alkali-soluble photoresist as described above, wherein the preparation of the photoresist comprises the following steps:
[0020] Add modified phenolic resin into a three-necked flask, add propylene glycol methyl ether acetate, and fully dissolve the resin under nitrogen protection and stirring at 30°C to obtain a uniform solution; slowly add modified acrylate to the uniform solution, and stir at 300rpm for 30min to obtain a mixed solution; slowly add a photosensitive substance to propylene glycol methyl ether acetate, and continue to stir and disperse uniformly to obtain a dispersion; slowly add the dispersion to the mixed solution, stir uniformly, then add silicone oil and stabilizer 1010, heat to 40°C and stir for 2h, filter with a filter membrane to remove impurities, and obtain a photoresist colloid;
[0021] The KH-792 is dissolved in a 95% ethanol solution, the pH value of the system is adjusted to 3 with acetic acid, and the mixture is stirred in a 50°C magnetic stirrer for 2 hours to obtain a silane coupling agent solution; nano-titanium dioxide is slowly added to the silane coupling agent solution, and the mixture is reacted for 2 hours to obtain a modified system; the modified system is dried and ground to obtain modified nano-titanium dioxide; the modified nano-titanium dioxide is added to the photoresist colloid, and the mixture is stirred at 200-400 rpm for 1-3 hours at 30-60°C, and the mixture is filtered through a filter membrane to remove impurities, and the photoresist is obtained.
[0022] Preferably, the preparation of the modified phenolic resin comprises the following steps:
[0023] The phenol compound, the aldehyde compound and the modifier are placed in a vacuum drying oven at 80°C for 2 hours to obtain a dry material; 20 parts of the phenol compound, the aldehyde compound and the modifier are added to a three-necked flask in sequence, the temperature is raised to 50°C and mixed evenly to obtain a mixed system; 30 parts of a 30% by mass sodium hydroxide solution are added to the mixed system, and the mixture is stirred for 10 minutes to obtain a reaction system; the reaction system is heated to 70°C and kept warm for reaction for 5 hours to obtain a reaction product; citric acid solution is added to the reaction product, the pH is adjusted to neutral, the mixture is left overnight, and centrifugally filtered and washed to obtain the modified phenolic resin; wherein the modifier accounts for 20% of the total mass of the phenolic resin.
[0024] Preferably, the preparation of the modified acrylate comprises the following steps:
[0025] Azobisisobutyronitrile is added into deionized water, and stirred evenly at 300 rpm to obtain an emulsion; the emulsion is added into a flask, and potassium persulfate is added at 100 rpm, and styrene acrylate, acrylic acid, and hexafluorophenylpropyl methacrylate are stirred to obtain a pre-emulsion; potassium persulfate is added into the pre-emulsion, and stirred at 200 rpm for 20 minutes under nitrogen protection to obtain a mixed system; the mixed system is heated to 80°C for reaction, and potassium persulfate is continuously added after blue light appears, and the mixture is kept warm for 10 minutes to obtain a reaction system; the reaction system is heated to 90°C, and the mixture is kept warm for 3 hours to obtain a reactant; the reactant is cooled and cooled to 40°C to obtain a reaction product; ammonia water is added into the reaction product to adjust the pH value to 7-8, and the gel is filtered through gauze to obtain the modified acrylate; wherein the mass ratio of styrene acrylate, acrylic acid and modifier 2 is 12:5:3.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention adjusts the types and usage ratios of phenolic compounds and aldehyde compounds, controls a type of modified phenolic resin obtained by reacting a modifier with a sodium hydroxide solution as a base resin of the photoresist, uses a modified acrylic resin obtained by two-step initiation polymerization of an acrylic monomer and a modifier as a cross-linking monomer, utilizes the conjugated structure of the benzene ring and the polar effect of the hydroxyl group to enhance the intermolecular force, forms a stable cross-linking structure, and improves the heat resistance of the photoresist.
[0028] 2. The present invention adjusts the types of modifier 1 and modifier 2, utilizes the introduction of phenyl-containing siloxane and fluorine-containing phenyl acrylate, and utilizes the stacking ability between the rigid conjugated systems of benzene rings to form a tight stack, cooperates with the effect of nano-titanium dioxide filling the gaps in the resin, slows down or prevents the intrusion of hydrofluoric acid solution from the edge and top of the interface where the glue and the substrate are combined, and achieves good hydrofluoric acid resistance. At the same time, the high hydrophobicity and high reactivity of the silicon-oxygen bond and the low surface energy of the fluorine atom can effectively resist the corrosion of hydrofluoric acid on the photoresist.
[0029] 3. The present invention controls the preparation method of modified acrylate, changes the type of acrylic monomer, uses modified acrylate to adjust the viscosity of the photoresist, and controls the type of solvent to cooperate with sodium diazonaphthoquinone sulfonate to improve the adhesion between the photoresist and the substrate, which helps to maintain the integrity of the photoresist pattern and make the generated graphics have good resolution.
[0030] 4. The present invention introduces modified nano-titanium dioxide into the photoresist colloid, controls the stirring parameters, and adjusts the mixing uniformity of the modified nano-titanium dioxide and the colloid by stirring and blending, so that the nano-titanium dioxide is fully filled in the resin gaps. After the hydrofluoric acid etching process, the surface-reacted nano-titanium dioxide cannot maintain the full filling of the photoresist resin structure gaps, and moisture and alkali molecules penetrate through the gaps into the resin structure, which promotes the breaking of chemical bonds in the resin structure, increases the alkali dissolution rate of degumming, and reduces the generation of pollutants and organic solvents during the degumming process. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The graph is a graph showing the variation of the mass retention rate with temperature for Example 1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0034] The KH-792 described in the present invention is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, CAS: 1760-24-3; the KH-570 described in the present invention is methacryloxypropyltrimethoxysilane, CAS: 2530-85-0.
[0035] See also Figure 1 The present invention provides a HF-resistant alkali-soluble photoresist and a preparation method thereof, and the technical scheme is as follows:
[0036] Example 1
[0037] Place α-naphthol, salicylaldehyde and terminal hydroxyl polydiphenylsiloxane in a vacuum drying oven at 80°C for 2 hours to obtain a dry material; add the phenylphenol, salicylaldehyde and terminal hydroxyl polydimethylsiloxane into a three-necked flask in sequence, heat to 50°C and mix evenly to obtain a mixed system; add 30 parts of a 30% sodium hydroxide solution by mass to the mixed system, stir for 10 minutes, and obtain a reaction system; heat the reaction system to 70°C, keep the temperature for 5 hours to obtain a reaction product; add citric acid solution to the reaction product, adjust the pH to neutral, leave it overnight, centrifuge and filter, wash to obtain a modified phenolic resin; wherein the terminal hydroxyl polydimethylsiloxane accounts for 20% of the total mass of the phenolic resin.
[0038] Add 5 parts of azobisisobutyronitrile to 20 ml of deionized water, and stir at 300 rpm to obtain an emulsion; add the emulsion to a flask, add 0.5 parts of potassium persulfate at 100 rpm, and stir 60 parts of styrene acrylate, 25 parts of acrylic acid, and 15 parts of hexafluorophenylpropyl methacrylate for 30 minutes to obtain a pre-emulsion; add 0.5 parts of potassium persulfate to the pre-emulsion, and stir at 200 rpm for 20 minutes under nitrogen protection to obtain a mixed system; heat the mixed system to 80°C for reaction, and continue to add 0.5 parts of potassium persulfate after blue light appears, and keep warm for 10 minutes to obtain a reaction system; heat the reaction system to 90°C and keep warm for 3 hours to obtain a reactant; cool the reactant to 40°C to obtain a reaction product; add ammonia water to the reaction product to adjust the pH value to 7-8, filter the gel with gauze, and obtain modified acrylate;
[0039] Add 60 parts of modified phenolic resin into a clean and dry three-necked flask, add 200 parts of propylene glycol methyl ether acetate, and fully dissolve the resin under nitrogen protection and stirring at 30°C to obtain a uniform solution; slowly add 20 parts of modified acrylate into the uniform solution, and stir at 300rpm for 30min to obtain a mixed solution; slowly add 10 parts of photosensitive material (including 2.5 parts of 2-hydroxy-2-methyl-1-phenylacetone and 7.5 parts of 1,4-diazonaphthoquinone) into propylene glycol methyl ether acetate, continue to stir and disperse evenly to obtain a dispersion; slowly add the dispersion into the mixed solution, stir at 200rpm, then add 5 parts of silicone oil and 10103 parts of stabilizer, heat to 40°C and stir for 2h, filter through a 0.2μm pore size filter membrane to remove impurity particles, and obtain a photoresist colloid;
[0040] Dissolve 5 parts of KH-792 in 95% ethanol solution, adjust the pH value of the system to 3 with acetic acid, and stir in a magnetic stirrer at 50°C for 2 hours to obtain a silane coupling agent solution; slowly add 30 parts of nano titanium dioxide into the silane coupling agent solution, react at 50°C for 2 hours to obtain a modified system; dry the modified system at 80°C for 2 hours, grind for 30 minutes to obtain modified nano titanium dioxide; add 10 parts of the modified nano titanium dioxide into 100 parts of the photoresist colloid, stir at 300rpm for 1 hour at 30°C, filter through a 0.2μm pore size filter membrane to remove impurity particles, and obtain an HF-resistant alkali-soluble photoresist.
[0041] Examples 2-10 refer to the preparation methods and parameter conditions of Example 1, with the differences shown in Table 1.
[0042] Table 1 Component changes of Examples 1-10
[0043]
[0044] Comparative Example 1 refers to the preparation method and parameter conditions of Example 1, except that terminal hydroxyl polydiphenylsiloxane is not added.
[0045] Comparative Example 2 refers to the preparation method and parameter conditions of Example 1, except that hexafluorophenylpropyl methacrylate is not added.
[0046] Comparative Example 3 refers to the preparation method and parameter conditions of Example 1, except that terminal hydroxyl polydiphenylsiloxane and hexafluorophenylpropyl methacrylate are not added.
[0047] Example 11 Heat resistance performance measurement
[0048] The HF-resistant alkali-soluble photoresists prepared in Examples 1-10 and Comparative Examples 1-2 were added to a hot pressing mold and cured at 80° C. for 40 min to obtain photoresist films. The thermal stability of the films was tested using a thermogravimetric analyzer TGA / Q50 (purchased from Mettler-Toledo Technology Co., Ltd.). 5 mg of the sample was taken and nitrogen was used for protection at a flow rate of 50 mL / min. The test temperature was 25-500° C. and the heating rate was 10° C. / min. T 5%( The temperature at which the weight loss rate is 5% and T 80%( The temperature when the weight loss rate is 80%), the results are shown in Table 1. Figure 1 The graph of the quality retention rate of Example 1 and Comparative Examples 1-3 as a function of temperature is shown.
[0049] Table 1 Determination of heat resistance of Examples 1-10 and Comparative Examples 1-2
[0050] Example <![CDATA[T5℃]]> <![CDATA[T 80 ℃]]> Example 1 188 322 Example 2 162 295 Example 3 174 308 Example 4 183 312 Example 5 155 282 Example 6 185 316 Example 7 187 318 Example 8 188 325 Example 9 164 302 Example 10 192 328 Comparative Example 1 128 268 Comparative Example 2 132 272 Comparative Example 3 103 252
[0051] pass Figure 1The results show that the weight loss of the prepared photoresist film mainly has three stages. The first stage is 50-200℃. During this stage, the material contains a small amount of H2O and incompletely reacted hydroxymethyl and ether bonds, which gradually react to form methylene during the heating process and the volatilization of H2O leads to weight loss; the second stage is 200-400℃, which is the main stage of weight loss of the photoresist film. This is because the modified phenolic resin and modified acrylate are cracked to form small molecules at high temperature; the third stage is that the quality tends to be stable after 400℃, and only inorganic components exist in the system at this time. From the results in Table 1, it can be seen that the heat resistance of the photoresist prepared in Comparative Example 3 without adding hydroxyl polydiphenylsiloxane and hexafluorophenylpropyl methacrylate is significantly lower than that in the embodiment. Due to the introduction of silicon-oxygen bonds and fluorine-containing groups, the heat resistance of the film is significantly improved; the heat resistance of Comparative Examples 1-2, in which only siloxane and fluorine-containing groups are added respectively, is slightly improved, but there is still a significant gap compared with Examples 1-10; From the results of Comparative Examples 1-6, it can be seen that the high temperature resistance of the phenolic resin formed by the polycondensation reaction of different phenols and aldehydes is different, and the use of salicylaldehyde and naphthol significantly increases the heat resistance. Due to the conjugated rigid structure of the benzene ring and the polar effect of the hydroxyl group, the intermolecular force is enhanced, and the conjugated effect of the benzene ring forms a stable cross-linked structure between the molecules. After heat curing treatment, The phenolic resin and the acrylate are further cross-linked to form a more stable methylene structure, thereby improving the thermal stability of the photoresist. The improvement in thermal stability is beneficial to the stability of the photoresist during the alkali-dissolving development process, and prevents the unexposed photoresist from being dissolved and removed by the hot alkali solution. By comparing the results of Example 1 and Examples 7-8, it can be seen that changing the phenolic molar ratio has little effect on the thermal stability of the photoresist, but excessive salicylaldehyde will lead to an increase in the content of free phenol in the system, which is easily oxidized under high temperature and affects the photolithography process. It can be seen from the results of Examples 1 and Examples 9-10 that with the increase in the amount of modified phenolic resin used, the heat resistance of the film is gradually improved, but the introduction of excessive modified phenolic resin reduces the adhesion of the photoresist, affects the application of the photoresist in the chain photolithography machine, and reduces the accuracy and resolution of the pattern.
[0052] Examples 12-19
[0053] Place α-naphthol, salicylaldehyde and a modifier in a vacuum drying oven at 80°C for 2 hours to obtain a dry material; add 80 parts of phenylphenol, furfural and 20 parts of terminal hydroxyl polydimethylsiloxane into a three-necked flask in sequence, heat to 50°C and mix evenly to obtain a mixed system; add 60 parts of a 30% sodium hydroxide solution by mass to the mixed system, stir for 10 minutes to obtain a reaction system; heat the reaction system to 70°C, keep the temperature for 5 hours to obtain a reaction product; add citric acid solution to the reaction product, adjust the pH to neutral, leave overnight, centrifuge and filter, wash to obtain a modified phenolic resin;
[0054] Add 5 parts of azobisisobutyronitrile to 20 ml of deionized water, and stir evenly at 300 rpm to obtain an emulsion; add the emulsion to a flask, add 0.5 parts of potassium persulfate at 100 rpm, and stir styrene acrylate, acrylic acid, and modifier 2 for 30 minutes to obtain a pre-emulsion; add 0.5 parts of potassium persulfate to the pre-emulsion, and stir at 200 rpm for 20 minutes under nitrogen protection to obtain a mixed system; heat the mixed system to 80° C. for reaction, and keep warm for 10 minutes after blue light appears to obtain a reaction system; heat the reaction system to 90° C. and keep warm for 3 hours to obtain a reactant; cool the reactant and cool it to 40° C. to obtain a reaction product; add ammonia water to the reaction product to adjust the pH value to 7-8, filter the gel with gauze, and obtain modified acrylate; the rest of the preparation process refers to Example 1, and the specific parameter details are shown in Table 3.
[0055] Table 3 Variation of the dosage of components in Examples 12-18
[0056]
[0057]
[0058] Comparative Example 1 refers to the preparation method and parameter conditions of Example 1, except that terminal hydroxyl polydiphenylsiloxane is not added.
[0059] Comparative Example 2 refers to the preparation method and parameter conditions of Example 1, except that hexafluorophenylpropyl methacrylate is not added.
[0060] Comparative Example 3 refers to the preparation method and parameter conditions of Example 1, except that terminal hydroxyl polydiphenylsiloxane and hexafluorophenylpropyl methacrylate are not added.
[0061] Comparative Example 4 refers to the preparation method and parameter conditions of Example 1, except that no modified nano-titanium dioxide is added.
[0062] Comparative Example 5 refers to the preparation method and parameter conditions of Example 1, except that modified nano-titanium dioxide is added during the preparation of the photoresist colloid.
[0063] Example 20 HF acid resistance performance test
[0064] The photoresists prepared in Examples 12-19 and Comparative Examples 1-5 were uniformly coated on silicon wafer samples by immersion method, placed in a 0.5 mol / LDE hydrofluoric acid solution, and taken out after immersion for 2 hours. The corrosion of the photoresist surface was observed under an optical microscope, the pattern edge roughness parameters were measured, and the integrity of the photoresist was evaluated. The test results are shown in Table 4.
[0065] Table 4 Hydrofluoric acid resistance test of Examples 12-18 and Comparative Examples 1-5
[0066]
[0067]
[0068] The results in Table 4 show that the photoresist obtained by not adding terminal hydroxyl polydiphenylsiloxane and hexafluorophenylpropyl methacrylate in Comparative Example 3 has significantly reduced hydrofluoric acid corrosion resistance compared with Example 12. The photoresist obtained by adding only siloxane or fluorine-containing acrylate in Comparative Examples 1-2 has improved corrosion resistance compared with Comparative Example 3. However, compared with Example 12, the high hydrophobicity and high reactivity of the silicon-oxygen bond in the terminal hydroxyl polydiphenylsiloxane are utilized to avoid direct reaction of hydrofluoric acid with the resin matrix, thereby improving the hydrofluoric acid corrosion resistance. The low surface energy of fluorine atoms in the fluorine-containing acrylate can form a dense hydrophobic film on the surface of the photoresist, and the formed carbon-fluorine bonds can effectively resist the entry of hydrofluoric acid into the photoresist and the erosion of the internal chemical bonds. The results of Comparative Examples 4-5 show that with the change of the addition method of modified nano titanium dioxide, the corrosion resistance of the photoresist is significantly affected. When the photoresist colloid is prepared, the co-existence of the modified nano titanium dioxide and the co-existence of the modified nano titanium dioxide are stirred at the end of the reaction. By mixing with modified nano titanium dioxide, the nanoparticles can be filled in the voids inside the resin. When eroded by hydrofluoric acid, HF can be dispersed and consumed. At the same time, titanium dioxide occupies the voids in the resin, preventing hydrofluoric acid from entering the interior of the resin structure through the voids and corroding the internal chemical bonds. As shown in the results of Examples 12-17, the use of a modifier containing a conjugated group is helpful to improve the hydrofluoric acid resistance. The introduction of the conjugated group can effectively fit the surface of the substrate to form a strong interfacial force, thereby enhancing the adhesion of the photoresist to the substrate. In addition, the relatively strong chemical inertness and the repulsive force of the conjugated system on negative fluoride ions are fully utilized to improve the acid resistance. At the same time, the rigid conjugated system of the benzene ring has the ability to stack, and a tight laminate can be formed, which cooperates with the effect of nano titanium dioxide filling the voids in the resin, slowing down or preventing the HF solution from invading from the interface edge and above where the glue and the substrate are combined, thereby achieving good acid resistance.
[0069] Examples 21-27 refer to the preparation method and parameter conditions of Example 12, and the differences are shown in Table 5.
[0070] Comparative Example 6 refers to the preparation method and parameter conditions of Example 12, except that no modified acrylate is added.
[0071] Comparative Example 7 refers to the preparation method and parameter conditions of Example 12, except that acrylic acid is not added.
[0072] Comparative Example 8 refers to the preparation method and parameter conditions of Example 12, except that the modified acrylate is not prepared by the stepwise addition method.
[0073] Comparative Example 9 refers to the preparation method and parameter conditions of Example 12, except that only 2-hydroxy-2-methyl-1-phenylacetone is used as the photosensitizer.
[0074] Comparative Example 10 refers to the preparation method and parameter conditions of Example 12, except that only sodium diazonaphthoquinone sulfonate is used as the photosensitizer.
[0075] Comparative Example 11 refers to the preparation method and parameter conditions of Example 12, except that toluene is used as the solvent.
[0076] Comparative Example 12 refers to the preparation method and parameter conditions of Example 12, except that isopropanol is used as the solvent.
[0077] Example 28 Adhesion Test
[0078] The silicon substrates after development of Examples 21-27 and Comparative Examples 6-12 were placed in an oven at 180°C for post-baking for 10 minutes. After cooling to room temperature, the photoresist film was scratched and then torn off three times with 3M tape. The surface condition was observed to evaluate the adhesion of the photoresist to the substrate, wherein no peeling was excellent; the peeling area was less than or equal to 5% of the scratched area was good; the peeling area was less than or equal to 15% of the scratched area was medium; the peeling area was greater than 15% was poor. The test results are shown in Table 5.
[0079] Table 5 Adhesion test of Examples 21-27 and Comparative Examples 6-12
[0080]
[0081] From the results in Table 5, it can be seen that the addition of modified acrylate can significantly improve the adhesion of the photoresist, and the introduction of acrylic acid can increase the cross-linking sites of the modified acrylate, increase more polar groups during the curing process of the photoresist, increase the compatibility of the modified acrylate with the modified phenolic resin, improve the formation of the cross-linked three-dimensional structure, and increase the adhesion of the photoresist to the silicon substrate; the modified acrylate directly prepared by the one-step method in Comparative Example 8 reacts rapidly in the system due to the rapid addition of the initiator, and the polymerization stability of the emulsion is enhanced, but the too fast reaction rate will lead to The viscosity of the acrylate latex particles increases, the viscosity increases significantly, a large amount of gel is generated, the monomer conversion rate is reduced, and the obtained modified acrylate has a large viscosity. During the preparation of the photoresist, the solubility of the modified phenolic resin in propylene glycol methyl ether acetate is affected. At the same time, the addition of the high-viscosity modified acrylate causes the viscosity of the photoresist to increase rapidly, reducing the coating uniformity of the photoresist and affecting the adhesion of the photoresist to the substrate. At the same time, the excessively high viscosity affects the volatilization of the solvent, and the photoresist remains in a relatively wet state on the surface of the substrate for a long time, reducing the adhesion. Compared with Example 21, the adhesion of Comparative Examples 9-10 is significantly reduced, and the photosensitive The addition of the agent triggers a chemical reaction between the groups in the photoresist. During the illumination process, 1,4-naphthoquinonediazo and 2-hydroxy-2-methyl-1-phenylacetone can release more free radicals, provide more cross-linked structures, and increase adhesion. The results of Example 12 and Comparative Examples 11-12 show that the change in the type of solvent further affects the adhesion of the photoresist. Toluene has poor solubility in modified acrylate, which leads to reduced coating uniformity and decreased adhesion of the photoresist during the preparation process. The introduction of isopropanol reduces the solubility in the modified phenolic resin, thereby reducing the cross-linking effect of the base resin and reducing the adhesion to the substrate. By using propylene glycol methyl ether acetate and taking advantage of its high compatibility, the viscosity of the photoresist can be adjusted. At the same time, its low surface tension helps the photoresist to better wet the surface of the substrate, thereby improving adhesion. By using propylene glycol methyl ether acetate in conjunction with modified acrylates, the adhesion between the photoresist and the substrate can be improved by adjusting the mass fraction and components of the photosensitizer. Good adhesion helps to maintain the integrity of the photoresist pattern and achieve high-resolution patterns. At the same time, the improvement in adhesion prevents the acid from corroding the photoresist through the edge of the interface between the photoresist and the substrate during the hydrofluoric acid etching process, thereby further improving the hydrofluoric acid resistance.
[0082] Embodiment 29
[0083] The preparation of photoresist colloid is referred to Example 12;
[0084] Dissolve 5 parts of KH-792 in 95% ethanol solution, adjust the pH value of the system to 3 with acetic acid, and stir in a magnetic stirrer at 50°C for 2 hours to obtain a silane coupling agent solution; slowly add 30 parts of nano titanium dioxide into the silane coupling agent solution, react at 50°C for 2 hours to obtain a modified system; dry the modified system at 80°C for 2 hours, grind for 30 minutes to obtain modified nano titanium dioxide; add 10 parts of the modified nano titanium dioxide into 100 parts of the photoresist colloid, stir at 300rpm for 2 hours at 30°C, filter through a 0.2μm pore size filter membrane to remove impurity particles, and obtain an HF-resistant alkali-soluble photoresist.
[0085] Examples 30-35 refer to the preparation method and parameter conditions of Example 29, and the differences are shown in Table 6.
[0086] Table 6 Parameter differences of Examples 29-35
[0087]
[0088] Comparative Example 13 refers to the preparation method and parameter conditions of Example 29, except that no modified nano-titanium dioxide is added.
[0089] Comparative Example 14 refers to the preparation method and parameter conditions of Example 29, except that modified nano-titanium dioxide is added during the preparation of the photoresist colloid.
[0090] Comparative Example 15 refers to the preparation method and parameter conditions of Example 29, except that KH-792 is not added for modification.
[0091] Comparative Example 16 refers to the preparation method and parameter conditions of Example 29, except that KH-570 is used for modification.
[0092] Comparative Example 17 refers to the preparation method and parameter conditions of Example 29, except that modified nano-silica is used.
[0093] Example 36 Alkali Solubility Test
[0094] After exposure, development and hydrofluoric acid etching, the photoresists prepared in Examples 30-35 and Comparative Examples 13-17 were placed in an alkaline solution of sodium hydroxide with a mass concentration of 5%, and the water bath temperature was maintained at 50°C. The time required for the photoresist to be completely dissolved, i.e., the alkali dissolution rate, was recorded; the flatness of the substrate surface after alkali dissolution was observed by atomic force microscopy (AFM) to determine whether there was residual photoresist and substrate damage caused by uneven dissolution; the test results are shown in Table 7.
[0095] Table 7 Alkali Solubility Test of Examples 30-35 and Comparative Examples 13-17
[0096] Example Alkali dissolution rate / s Residual photoresist evaluation Embodiment 29 15 No obvious residue, clean surface Embodiment 30 18 No obvious residue, clean surface Embodiment 31 20 No obvious residue, clean surface Embodiment 32 16 No obvious residue, clean surface Embodiment 33 14 No obvious residue, clean surface Embodiment 34 18 No obvious residue, clean surface Embodiment 35 14 No obvious residue, clean surface Comparative Example 13 78 There is a lot of residue, and there is a slight risk of damage to the substrate Comparative Example 14 45 There is a small amount of residue, which needs to be cleaned again Comparative Example 15 58 There is a lot of residue, and there is a slight risk of damage to the substrate Comparative Example 16 66 There is a lot of residue, and there is a slight risk of damage to the substrate Comparative Example 17 75 There is a lot of residue, and there is a slight risk of damage to the substrate
[0097] As shown in Table 7, the photoresists prepared by not adding modified nano-titanium dioxide or adding modified nano-silicon dioxide in Comparative Examples 13 and 17 are subjected to exposure, development and hydrofluoric acid etching, and the alkali dissolution rate is significantly improved compared with Example 29, and the alkali solubility is poor, which affects the photoresist degumming and degumming process, and there is still photoresist residue on the surface, which increases the impact on the subsequent processing technology. The addition of photosensitizer causes the photosensitizer in the system to undergo photodegradation reaction during the exposure process of the photoresist, and the generated free radicals change the chemical bonds of the resin, while increasing the dissolution and dispersion of the resin in the solvent, increasing the alkali solubility, and the unexposed resin utilizes the filling effect of nano-titanium dioxide on the resin gap and the strong intermolecular force between the resins to reduce the solubility while avoiding the erosion of the basic groups. During the hydrofluoric acid etching process, nano titanium dioxide is filled in the void structure of the resin material, filling the voids to increase the corrosion resistance of the photoresist to hydrofluoric acid. During the hydrofluoric acid etching process, part of the titanium dioxide reacts with the hydrofluoric acid, and the dense film structure formed by the generated product further improves the corrosion resistance to hydrofluoric acid. After the etching process, the surface-reacted nano titanium dioxide cannot keep the voids of the photoresist resin structure fully filled, and moisture and alkali molecules penetrate the voids into the resin structure, which promotes the breaking of the chemical bonds in the resin structure and increases the alkali dissolution rate. Comparative Examples 15-16 add a modifier to increase the combination of nano titanium dioxide and the matrix resin. force, making the filling of nano titanium dioxide more firmly and avoiding dissolution during acid etching. At the same time, the addition of the modifier avoids the agglomeration of nano titanium dioxide and avoids the agglomeration of nano titanium dioxide during alkali dissolution, which reduces the solubility of the photoresist in the alkaline solution and increases the residual photoresist during alkali dissolution and degumming, affecting the subsequent processing technology; the results of Examples 29-35 show that controlling the amount of modified nano titanium dioxide and changing the process parameters of the photoresist and nano titanium dioxide blending have little effect on the residual photoresist, and there is no photoresist residue on the surface. The amount of modified nano titanium dioxide increases the alkali dissolution time and affects the dissolution rate of the photoresist in the alkaline solvent.
[0098] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A HF-resistant and alkali-soluble photoresist, characterized in that: The photoresist comprises photoresist colloid and modified nano titanium dioxide; The photoresist colloid comprises 45-75 parts of modified phenolic resin, 12-25 parts of modified acrylate, 5-15 parts of photosensitizer, 160-240 parts of solvent and emulsion auxiliary agent; The modified phenolic resin is prepared by a phenol compound, an aldehyde compound and a modifier 1; the modified acrylate is prepared by styrene acrylate, acrylic acid and a modifier 2; The mass ratio of the photoresist colloid to the modified nano titanium dioxide is 8-12:1; The emulsion auxiliary agent includes silicone oil and antioxidant 1010.
2. The HF-stripping alkali-soluble photoresist according to claim 1, characterized in that: The phenol compound is selected from one of α-naphthol, nonylphenol, phenol and phenylphenol; the aldehyde compound is selected from one of salicylaldehyde, formaldehyde and furfural; the molar ratio of the phenol compound to the aldehyde compound is 1:1.2-1.
8.
3. The HF-stripping alkali-soluble photoresist according to claim 1, characterized in that: The mass ratio of the modified phenolic resin to the modified acrylic ester is 1-5:1; and the solvent is propylene glycol methyl ether acetate.
4. The HF-stripping alkali-soluble photoresist according to claim 1, characterized in that: The first modifier is selected from one of terminal hydroxyl polydiphenylsiloxane, terminal hydroxyl polyphenylmethylsiloxane and terminal hydroxyl polydimethylsiloxane; the second modifier is selected from one of hexafluorophenylpropyl methacrylate, perfluorooctyl ethyl acrylate and methacrylic acid.
5. The HF-stripping alkali-soluble photoresist according to claim 1, characterized in that: The photosensitizer is a mixture of 2-hydroxy-2-methyl-1-phenylacetone and sodium diazonaphthoquinone sulfonate; the mass ratio of the 2-hydroxy-2-methyl-1-phenylacetone to the sodium diazonaphthoquinone sulfonate is 1-5:
1.
6. A method for preparing a HF-resistant and alkali-soluble photoresist as claimed in claim 1, characterized in that: The preparation of the photoresist comprises the following steps: Add modified phenolic resin into a three-necked flask, add propylene glycol methyl ether acetate, and fully dissolve the resin under nitrogen protection and stirring at 30°C to obtain a uniform solution; slowly add modified acrylate to the uniform solution, and stir at 300rpm for 30min to obtain a mixed solution; slowly add a photosensitive substance to propylene glycol methyl ether acetate, and continue to stir and disperse uniformly to obtain a dispersion; slowly add the dispersion to the mixed solution, stir uniformly, then add silicone oil and stabilizer 1010, heat to 40°C and stir for 2h, filter with a filter membrane to remove impurities, and obtain a photoresist colloid; The KH-792 is dissolved in a 95% ethanol solution, the pH value of the system is adjusted to 3 with acetic acid, and the mixture is stirred in a 50°C magnetic stirrer for 2 hours to obtain a silane coupling agent solution; nano-titanium dioxide is slowly added to the silane coupling agent solution, and the mixture is reacted for 2 hours to obtain a modified system; the modified system is dried and ground to obtain modified nano-titanium dioxide; the modified nano-titanium dioxide is added to the photoresist colloid, and the mixture is stirred at 200-400 rpm for 1-3 hours at 30-60°C, and the mixture is filtered through a filter membrane to remove impurities, and the photoresist is obtained.
7. The method for preparing the HF-resistant alkali-soluble photoresist according to claim 6, characterized in that: The preparation of the modified phenolic resin comprises the following steps: The phenol compound, the aldehyde compound and the modifier are placed in a vacuum drying oven at 80°C for 2 hours to obtain a dry material; the phenol compound, the aldehyde compound and the modifier are added to a three-necked flask in sequence, the temperature is raised to 50°C and mixed evenly to obtain a mixed system; a 30% by mass sodium hydroxide solution is added to the mixed system, and the mixture is stirred for 10 minutes to obtain a reaction system; the reaction system is heated to 70°C and kept warm for 5 hours to obtain a reaction product; a citric acid solution is added to the reaction product, the pH is adjusted to neutral, the mixture is left overnight, and the mixture is centrifugally filtered and washed to obtain the modified phenolic resin; wherein the modifier accounts for 20% of the total mass of the phenolic resin.
8. The method for preparing the HF-resistant alkali-soluble photoresist according to claim 6, characterized in that: The preparation of the modified acrylate comprises the following steps: Azobisisobutyronitrile was added into deionized water, and stirred evenly at 300 rpm to obtain an emulsion; the emulsion was added into a flask, and potassium persulfate was added at 100 rpm, and styrene acrylate, acrylic acid, and modifier 2 were stirred to obtain a pre-emulsion; potassium persulfate was added into the pre-emulsion, and stirred at 200 rpm for 20 minutes under nitrogen protection to obtain a mixed system; the mixed system was heated to 80°C for reaction, and potassium persulfate was continuously added after blue light appeared, and the mixture was kept warm for 10 minutes to obtain a reaction system; the reaction system was heated to 90°C, and the mixture was kept warm for 3 hours to obtain a reactant; the reactant was cooled and cooled to 40°C to obtain a reaction product; ammonia water was added into the reaction product to adjust the pH value to 7-8, and the gel was filtered with gauze to obtain the modified acrylate; wherein the mass ratio of styrene acrylate, acrylic acid, and modifier 2 was 12:5:3.
Citation Information
Patent Citations
Positive-type photosensitive resin composition, method for producing resist pattern, semiconductor device, and electronic device
CN102257431A
Photoresist composition
CN110441989A
High-temperature-resistant positive photoresist
CN112631076A
HF-acid-etching-resistant strong-alkali-annealing photoresist and preparation method thereof
CN118567185A
Cited By
A mask composition, a mask pattern detection method and a battery piece intermediate
CN122632523A